Penapisan Ketahanan Galur Tomat terhadap Tomato chlorosis crinivirus - Wahyudin, Denih; Damayanti, Tri Asmira; Mutaqin, Kikin Hamzah (Jurnal Fitopatologi Indonesia, 2022)
Screening for Resistance of Tomato Lines Against Tomato chlorosis crinivirus Infection of Tomato chlorosis crinivirus (ToCV) has been reported involved in yellow disease of tomato. Recently, incidence of Crinivirus is increasing in tomato growing areas in West Java. Growing resistant tomato varieties will be effective for viral disease management, although finding resistance sources is quite a challenge. The aim of the study was to determine the resistance level of 12 tomato lines to ToCV infection. Fourteen days after transplanting, tomato lines were inoculated with ToCV using 10 viruliferous whiteflies (Trialeurodes vaporariorum). Observations were made on disease variables (incubation period, incidence and severity of disease, virus titer) and agronomic variables (plant height, number of leaves, number and weight of fruits). The average incubation period ranged from 9.4–13.5 days, and disease incidence ranged from 90.9–100%. Visual symptoms varied from mild to moderate chlorosis and leaf curling with disease severity scores ranging from 1.0–3.0. Virus titers were measured based on ELISA’s absorbance values, which ranged from 0.358 to 1.122. In general, ToCV infection inhibited plant growth and decreased leaf number, inhibited fruit weight and number i.e.  6.0–37.8%, 8.6–39.5%, 2.7–33.7%, and 7.0–25.5%, respectively. Based on disease assessement paramaters, responses of tomato lines were categorized as susceptible (BISILB#1029A, BISILB#22, and BISILB#724B), moderate resistant (BISILB#825B, BISILB#60D, BISIKC#402, BISIKC#96D, and BISILB#40I), and resistant (BISILB#1372ORA, BISILB#703A, BISILB#703B, and BISILB#724A). However, the resistance trait showed no correlation with tomato yield. Therefore, it is necessary to improve the trait of four resistant genotype so that is more adaptive to cultivation environmental factors and can be utilized as the parent of elite ToCV-resistant tomato variety.